2013
DOI: 10.5935/abc.20130111
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac I123-MIBG Correlates Better than Ejection Fraction with Symptoms Severity in Systolic Heart Failure

Abstract: BackgroundThe association of autonomic activation, left ventricular ejection fraction (LVEF) and heart failure functional class is poorly understood. ObjectiveOur aim was to correlate symptom severity with cardiac sympathetic activity, through iodine-123-metaiodobenzylguanidine (123I-MIBG) scintigraphy and with LVEF in systolic heart failure (HF) patients without previous beta-blocker treatment. MethodsThirty-one patients with systolic HF, class I to IV of the New York Heart Association (NYHA), without previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…123 I-MIBG is a recently developed method for assessing inappropriate cardiac sympathetic activity [28]. Numerous studies, including meta-analyses, have demonstrated that both a low early or delayed H/M ratio and an increased WR are associated with advanced stages of HF and a high incidence of fatal arrhythmia, mortality, and morbidity [8][9][10][11][12][13][14][15][16][17][18]. I-MIBG has furthermore proven to be a predictor of both good responses to b-blocker treatment and successful cardiac resynchronization therapy [19,20].…”
Section: I-mibg and Cardiac Sympathetic Reservementioning
confidence: 99%
See 1 more Smart Citation
“…123 I-MIBG is a recently developed method for assessing inappropriate cardiac sympathetic activity [28]. Numerous studies, including meta-analyses, have demonstrated that both a low early or delayed H/M ratio and an increased WR are associated with advanced stages of HF and a high incidence of fatal arrhythmia, mortality, and morbidity [8][9][10][11][12][13][14][15][16][17][18]. I-MIBG has furthermore proven to be a predictor of both good responses to b-blocker treatment and successful cardiac resynchronization therapy [19,20].…”
Section: I-mibg and Cardiac Sympathetic Reservementioning
confidence: 99%
“…However, definitive preoperative predictors of this remodeling have not yet been identified. 123 I-metaiodobenzylguanidine ( 123 I-MIBG) is an analog of guanethidine [6] used either to stratify the severity of heart failure (HF) or to predict HF patient prognosis by assessing visualized cardiac sympathetic innervation [7][8][9][10][11][12][13][14][15][16][17][18]. Moreover, 123 I-MIBG has recently been adopted as a tool for predicting or confirming the clinical response to bblocker treatment as well as cardiac resynchronization therapy [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…It was detected that H/M ratio and WR correlates better with gravity of symptoms and NYHA functional class than ejection fraction in patients with HF without previous treatment with betablocker (16).…”
Section: I-mibg and Exercise Tolerancementioning
confidence: 99%
“…Cardiac imaging with 123 I-metaiodobenzylguanidine ( 123 I-MIBG), an analogue of norepinephrine, is a useful tool for detecting abnormal cardiac sympathetic nervous activity in heart failure (HF) patients [36]. Increased sympathetic nervous activity in DCM patients is shown to be associated with a poor prognosis [79]…”
Section: Introductionmentioning
confidence: 99%